The relationship between preeclampsia and periodontal pathology - Dmitry I. Trukhan; Anatoly F. Sulimov; Larisa Yu. Trukhan (LLC "MEDIAFORMAT", 2023)
Preeclampsia is a pregnancy-specific hypertension associated with systemic multiple organ damage that remains the leading cause of maternal and infant mortality worldwide. Chronic inflammatory diseases of the periodontium (gingivitis, periodontitis) occupy the 2nd place after caries in terms of prevalence among dental diseases. Periodontal pathology in the domestic literature is not currently considered as a risk factor for the development of preeclampsia. The present review considers clinical studies and reviews presented in the PubMed information base, which discuss the relationship between preeclampsia and periodontal disease. Based on the analysis of clinical studies, reviews and meta-analyses, a bidirec-tional relationship between preeclampsia and periodontal disease can be assumed. The main possible mechanisms of the relationship between preeclampsia and periodontal pathology are considered. The data presented in the review certainly require comprehension by both dentists and obstetricians-gynecologists and internists. But they clearly indicate the need to identify and actively treat dental diseases even at the stage of pre-conception preparation, as well as during pregnancy.